(untitled) (Research, Society and Development, 2022)
Objective: to provide an anatomical description of the palatal region, both hard palate and soft palate, describing its irrigation and innervation through a tomographic approach and illustrations of its structures, synthesizing the criteria of several authors after a bibliographic review. Methods: the literature review was performed using information from books of human anatomy, human embryology, oral and maxillofacial surgery and scientific articles from the following databases: Medical Literature Analysis and Retrieval System Online (Medline), Literatura Latinoamericana y del Caribe en Ciencias de la Salud (LILACS) and Scientific Electronic Library Online (SciELO). These databases were found in the Regional Documentation Center Juan Bautista Vázquez, (library of the University of Cuenca). Results: a search using keywords and Boolean operators yielded a database with 4,120 articles. Then, 25 articles were analyzed after applying inclusion and exclusion criteria. Subsequently, a total of 16 books of human anatomy, human embryology, oral and maxillofacial surgery were analyzed, of which 11 were excluded due to repetitive and incomplete information on the anatomical region under study. Conclusions: the palatal region is a very vascularized and innervated area formed by a hard structure located in the anterior area of the palate and a soft structure in the posterior area, as well as vascular, nervous, muscular, mucous, membranous and glandular elements. By knowing the normal anatomy of this region, it will be possible to efficiently identify pathologies or alterations that may affect it.